2018
DOI: 10.5021/ad.2018.30.2.202
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Effects of Bee Venom Components onTrichophyton rubrum: A Novel Approach of Bee Venom Study for Possible Emerging Antifungal Agent

Abstract: BackgroundBee venom (BV) has been widely investigated for potential medical uses. Recent inadvertent uses of BV based products have shown to mitigate signs of fungal infections. However, the component mediating the antifungal effect has not been identified.ObjectiveThis investigation compares bee venom in its whole and partial forms to evaluate the possible component responsible for the antifungal effect.MethodsForty-eight plates inoculated with Trichophyton rubrum were allocated into four groups. The groups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 18 publications
(40 reference statements)
0
20
0
Order By: Relevance
“…In the study of Park et al that investigated the antifungal effects of BV, mellitin, apamin, and BV-based mists on T. rubrum indicated that BV and BV-based mist exhibited strong antifungal effect on T. rubrum . However, the isolated BV components, such as mellitin and apamin, showed no significant effect in hindering the growth of the fungal colonies [101].…”
Section: Inhibitory Effects Of Bv Against Pathogenic Agent Which Imentioning
confidence: 99%
“…In the study of Park et al that investigated the antifungal effects of BV, mellitin, apamin, and BV-based mists on T. rubrum indicated that BV and BV-based mist exhibited strong antifungal effect on T. rubrum . However, the isolated BV components, such as mellitin and apamin, showed no significant effect in hindering the growth of the fungal colonies [101].…”
Section: Inhibitory Effects Of Bv Against Pathogenic Agent Which Imentioning
confidence: 99%
“…Melittin displays strong membrane-perturbing activity, which is responsible for its anti-microbial [ 13 ], antiviral [ 14 ], antifungal [ 15 ], and anticancer [ 16 ] activities. When several melittin molecules penetrate into the cell membrane, they break down the phospholipids leading to cell lysis.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the pigment disorders, the bee venom seems to intervene as well in the negative and positive regulation of the melanogenesis, thus according to certain authors and in addition to its anti-aging and brightening effect, the venom of bee inhibits the enzymes of melanogenesis including tyrosinase and tyrosinase-related protein 1 and 2 (TRP-1 and TRP-2) and inhibit the effect of alpha MSH on melanoma B16F1 cells [7][8][9][10][11][12][13][14][15][16][17][18][19][20], and according to other authors, bee venom stimulates proliferation of human melanocytes, melanogenesis, proliferation of dendrites and migration and transfer of melanosomes [8].…”
Section: Discussionmentioning
confidence: 99%
“…Sporadic studies show the interest of bee venom in the improvement of acne lesions, in the treatment of onychomycosis and in the regulation of the immune system in general [11][12][13].…”
Section: Discussionmentioning
confidence: 99%